Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.4095/204885
|View full text |Cite
|
Sign up to set email alerts
|

Drift composition and glacial dispersal trains, Baker Lake area, District of Keewatin, Northwest Territories

Abstract: In the District of Keewatin, glacial dispersal trains defined by lithology and geochemistry are mapped at regional (hundreds of kilometres), local (tens of kilometres), and detailed (kilometres) scales. The trains reflect glacial dynamics and the bedrock composition. Despite complex ice flow near the Keewatin Ice Divide, they have a prominent southeastward trend, although there is evidence for older regional southward and eastward flows, and for later flow northward and westward from the divide. In till, trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In the 1990s, Clark (1990a, 1990b) used satellite imagery over North America to reveal crossing drift lineations, namely in the area of the Keewatin Ice Divide, and to infer mobility of outflow centres within the Laurentide Ice Sheet throughout the last glacial cycles. Based on till composition near Baker Lake, Klassen (1995Klassen ( , 2001 showed strong evidence for southeastward dispersal under the Keewatin Ice Divide area, hence supporting the southeastward migration of the divide. Based on the examination of stratigraphic sections of till along the Kazan River, Klassen (1995) observed differences in provenance related to changes in the location and orientation of the Keewatin Ice Divide, but he also reported that correlations with overburden drill-core information in the area (i.e.…”
Section: Previous Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…In the 1990s, Clark (1990a, 1990b) used satellite imagery over North America to reveal crossing drift lineations, namely in the area of the Keewatin Ice Divide, and to infer mobility of outflow centres within the Laurentide Ice Sheet throughout the last glacial cycles. Based on till composition near Baker Lake, Klassen (1995Klassen ( , 2001 showed strong evidence for southeastward dispersal under the Keewatin Ice Divide area, hence supporting the southeastward migration of the divide. Based on the examination of stratigraphic sections of till along the Kazan River, Klassen (1995) observed differences in provenance related to changes in the location and orientation of the Keewatin Ice Divide, but he also reported that correlations with overburden drill-core information in the area (i.e.…”
Section: Previous Researchmentioning
confidence: 99%
“…The dispersal of Dubawnt erratics as far south as the Manitoba border provides a better support for southward glacial transport in the region. Geochemical composition of till collected in the lower parts of drill core south of Pitz Lake also point to an early southward flow (Klassen, 1995).…”
Section: South-southeasterly Flowmentioning
confidence: 99%
See 3 more Smart Citations